2020
DOI: 10.1016/j.exger.2019.110820
|View full text |Cite
|
Sign up to set email alerts
|

IDO activation, inflammation and musculoskeletal disease

Abstract: The IDO/kynurenine pathway is now established as a major regulator of immune system function. The initial enzyme, indoleamine 2,3-dioxygenase (IDO1) is induced by IFNγ, while tryptophan-2,3-dioxygenase (TDO) is induced by corticosteroids. The pathway is therefore positioned to mediate the effects of systemic inflammation or stress-induced steroids on tissue function and its expression increases with age. Disorders of the musculoskeletal system are a common feature of aging and many of these conditions are char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 100 publications
1
24
0
2
Order By: Relevance
“…These results were in accordance with earlier findings that reported that inflammation causes the upregulation of IDO activity and leads to increased tryptophan catabolism via the kynurenine pathway [68]. On the other hand, in inflammatory arthritis and related disorders, kynurenine protects against the development of disease, while the inhibition or deletion of IDO increases its severity [84]. Similarly, the results from a recent study in hemodialysis patients suggested that the low tryptophan values in this patient group could not be attributed to high IDO activity or an inflammatory state [85].…”
Section: The Essential Amino Acid Tryptophansupporting
confidence: 93%
“…These results were in accordance with earlier findings that reported that inflammation causes the upregulation of IDO activity and leads to increased tryptophan catabolism via the kynurenine pathway [68]. On the other hand, in inflammatory arthritis and related disorders, kynurenine protects against the development of disease, while the inhibition or deletion of IDO increases its severity [84]. Similarly, the results from a recent study in hemodialysis patients suggested that the low tryptophan values in this patient group could not be attributed to high IDO activity or an inflammatory state [85].…”
Section: The Essential Amino Acid Tryptophansupporting
confidence: 93%
“…In addition, an increased TDO expression was described in many tumor types, for example, breast cancer, melanoma or lung cancer [35,36] (Table 1). The main determinant of TRP availability is the TDO enzyme, the expression of TDO can be stimulated by estrogens, corticosteroids, heme, as well as TRP itself [35,56,57]. NADH and NADPH inhibit TDO expression through a negative feedback loop [54] (Table 1, Figure 3).…”
Section: Tryptophan 23-dioxygenasementioning
confidence: 99%
“…В настоящее время согласно EWGSOP2 в зависимости от этиологии саркопению подразделяют на первичную (agerelated sarcopenia -возрастассоциированную саркопению) и вторичную саркопению (disease-related sarcopenia -саркопению, ассоциированную с заболеванием) [5,7,8]. Основным патогенетическим механизмом развития вторичной саркопении является стойкое повышения уровня провоспалительных цитокинов в крови, в том числе интерлейкина-6, фактора некроза опухоли α. В связи с этим особый интерес представляет оценка распространенности саркопении у пациентов с ревматологической патологией, для которых в целом характерно значительное стойкое повышение уровня провоспалительных цитокинов [9].…”
Section: Original Articleunclassified